Granulated straw incorporation with rotary tillage increases the content of soil organic carbon fractions and available nutrients and shifts bacterial communities in East China - Dong, Jianxin; Wang, Ping; Cong, Ping; Song, Wenjing; Zheng, Xuebo; Liu, Na; Wang, Yi; Xiao, Xin; Zhai, Zhen; Li, Yuyi; Pang, Huancheng (Frontiers in Plant Science, 2025)
IntroductionGranulated straw incorporation is a novel approach designed to enhance straw decomposition and improve soil fertility. However, the effects of different straw incorporation amounts under deep tillage and rotary tillage on soil available nutrients, soil organic carbon (SOC) fractions, bacterial communities, and crop yield remain unclear.MethodsIn a 3-year field experiment, three granulated maize straw amounts (G1, 2,250; G2, 4,500; and G3, 6,750 kg hm−2) and two tillage methods (T, deep tillage; and R, rotary tillage) were applied to evaluate their impacts on SOC fractions, available nutrients, bacterial communities, and flue-cured tobacco yield.Results and DiscussionCompared with conventional tillage (RG0), granulated straw incorporation significantly increased SOC content. Over the 3 years, the SOC content in the 0–20 and 20–40 cm soil layers increased by 4.40%–23.46% and 5.36%–39.21% (p < 0.05), respectively. Moreover, the incorporation of higher straw amounts significantly increased the content of dissolved organic carbon (DOC) and microbial biomass carbon (MBC). Specifically, the RG3 treatment significantly increased DOC content in both soil layers in 2016 and 2017, while TG3 showed the greatest increase in 2018. In addition, RG2 and RG3 consistently enhanced MBC content across both layers throughout the 3 years. During the tobacco growing period, soil ammonium nitrogen (NH4+–N), nitrate nitrogen (NO3−–N), and available potassium (AK) contents increased with higher straw amounts in both soil layers. The RG2 treatment notably enhanced the bacterial α diversity and increased the relative abundance of phyla Firmicutes and Gemmatimonadota in the 20–40-cm layer. Network analysis identified AK as a key nutrient influencing bacterial community structure under both tillage methods. Structural equation modeling further revealed that SOC fractions were primarily regulated by nutrient factors under rotary tillage, while under deep tillage, bacterial richness and AK played dominant roles. To improve soil quality and crop productivity, the incorporation of a medium amount of granulated straw combined with rotary tillage is recommended as a sustainable practice for flue-cured tobacco cultivation.